Unique palliative care needs of patients with advanced chronic kidney disease – the scope of the problem and several solutions - Sturgill, Daniel (Clin Med (Lond), 2019)
Patients with advanced chronic kidney disease (CKD), including end-stage renal disease (ESRD), have a life-threatening illness complicated by high morbidity and mortality and, therefore, should be suitable candidates for early intervention by palliative care specialists. However, the average patient with CKD does not have an advanced care plan, has multiple debilitating symptoms, and does not utilise hospice care at the end of life. In this review, we outline the scope of the problem of unmet palliative care needs for patients with advanced CKD and ESRD, barriers to improving palliative care for patients with renal failure, and possible future directions for palliative nephrology.